2011
DOI: 10.1161/atvbaha.110.220988
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proprotein Convertase Subtilisin/Kexin 9 (PCSK9) Regulates VLDLR Protein and Triglyceride Accumulation in Visceral Adipose Tissue

Abstract: Objective-Proprotein convertase subtilisin/kexin 9 (PCSK9) promotes the degradation of the low-density lipoprotein receptor (LDLR), and its gene is the third locus implicated in familial hypercholesterolemia. Herein, we investigated the role of PCSK9 in adipose tissue metabolism. Methods and Results-At 6 months of age, Pcsk9Ϫ/Ϫ mice accumulated Ϸ80% more visceral adipose tissue than wild-type mice. This was associated with adipocyte hypertrophy and increased in vivo fatty acid uptake and ex vivo triglyceride s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
170
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(191 citation statements)
references
References 29 publications
(44 reference statements)
13
170
2
1
Order By: Relevance
“…For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9. 42 The receptors LDLR, VLDLR, and ApoER2 have been confirmed as PCSK9 target proteins in mice 25,26,65,66 and the LDLR in monkeys 67 and human. 68 Recently, we showed that PCSK9 can enhance the degradation of LRP1 in various cells 44 although proof of this activity in vivo is still lacking.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, in contrast to the LDLR, the GOF D374Y PCSK9 does not degrade these other receptors more efficiently than wild-type PCSK9. 42 The receptors LDLR, VLDLR, and ApoER2 have been confirmed as PCSK9 target proteins in mice 25,26,65,66 and the LDLR in monkeys 67 and human. 68 Recently, we showed that PCSK9 can enhance the degradation of LRP1 in various cells 44 although proof of this activity in vivo is still lacking.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 96%
“…Finally, CD36, a scavenger receptor with multiple ligands and cellular functions, including facilitating cellular uptake of free fatty acids (FFA), was also suspected to be a PCSK9 target in intestinal epithelial cells 69 and adipose tissue. 65 Recently, this PCSK9 activity on CD36 was elegantly proven in cells and adipocytes. 70 because the structures of CD36 or CD81 (see below) do not exhibit an EGF-A-like domain, their respective sequences that bind PCSK9 either directly or indirectly have yet to be defined.…”
Section: Other Pcsk9 Target Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, circulating PCSK9 down‐regulates LDLR expression on the hepatocyte surface, thus decreasing LDL catabolism and increasing plasma LDL‐cholesterol (LDL‐C) levels 18, 19. Although there is evidence that PCSK9 decreases VLDLR expression in adipose tissue 20, whether such a down‐regulation may occur in the liver is not established and the potential impact of PCSK9‐mediated change in VLDLR expression on HCV infection is still unknown. In addition, a significant down‐regulation of SR‐B1 gene was induced by PCSK9 21, 22, although its impact on HCV life cycle and replication needs to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, decreased production of triglyceride-rich lipoproteins and upregulation of VLDL receptors may also contribute to the triglyceride lowering (7,14). VLDL receptor expression is increased in visceral adipose tissue of PCSK9 null mice, leading to an 80% increase in visceral adiposity (15). Intracellular degradation of apolipoprotein receptor 2 (ApoER2) is increased by PCSK9 (14).…”
mentioning
confidence: 99%